Electronic Commerce Applications among Indian Small and Medium Enterprises - Asghar Afshar Jahanshahi; Seyed Mohammad Sadeq Khaksar .; Bairagi Kachardas Pitamber . (Information Management and Business Review, 2011)
The cutting edge for business today is electronic commerce. The main vehicle of electronic commerce unequivocally is the Internet and the World Wide Web. With the rapid advancement in the Internet software and hardware and the infrastructure, the electronic commerce is also becoming more and more popular. Many large corporations, small and medium companies and individuals are investing more and more in the Internet business. The main purpose of this paper is to study the effect of e-commerce applications on the operational performance of small and medium enterprises. There are many different types of e-commerce usages that may influence operational performances; in this research we group them according to five different categories: electronic advertising, payment system, marketing, customer support service, order and delivery. For analyzing the data derived from questionnaire, Goodness of Fit Tests and Structural Equation Modeling/Path Analysis were used and the software’s which has been used for analyzing the data were LISREL 8.54 and SPSS 18. Survey is considered to be the most appropriate and suitable for this study. According to statistical analysis in this research the results indicates that the electronic commerce applications has been influential on the operational performance in the Indian SMEs.